2011
DOI: 10.1183/09031936.00013311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an ambulatory diagnostic and treatment programme in patients with sleep apnoea

Abstract: The aim of this study to evaluate the efficacy of a home-based programme on clinical response, continuous positive airway pressure (CPAP) compliance and cost in a population of high pre-test probability of suffering obstructive sleep apnoea syndrome (OSAS).Patients were randomised into the following three groups. Group A: home respiratory polygraphy (RP) and home follow-up; group B: hospital polysomnography and hospital followup; and group C: home RP and hospital follow-up. Evaluation during 6 months included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 53 publications
1
46
0
1
Order By: Relevance
“…[83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration). [83][84][85]110 This subset of studies will be referred to as "RCTs most generalizable to clinical practice" for the remainder of this discussion section.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration). [83][84][85]110 This subset of studies will be referred to as "RCTs most generalizable to clinical practice" for the remainder of this discussion section.…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85][107][108][109][110] The meta-analysis showed a clinically and statistically insignificant difference of 0.38 points (95% CI: −1.07 to 0.32 points) greater improvement in patients randomized to the HSAT pathway versus the attended PSG pathway. This difference indicates that subjective sleepiness is similarly improved in patients who initiate PAP treatment based on diagnosis using either HSAT or PSG.…”
Section: Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…None of the studies found significant differences in disease management parameters. [77][78][79]92,93,99,102,103 In most of the studies, patients underwent both level 1 and level 3 tests to avoid the risk of internal bias due to differences between study groups. In all of the simultaneous studies, level 3 tests were scored manually by the same technician who scored the level 1 test, which may have resulted in observer bias.…”
Section: Diagnostic Accuracy Of Sleep Testsmentioning
confidence: 99%